Apotropaic Figurines from Nimrud (Calah) in the Australian Institute of Archaeology Collection - Siddall, Luis R. (Buried History: The Journal of the Australian Institute of Archaeology, 2022)
There are two clay figurines in the Australian Institute of Archaeology’s collection, which were excavated by the British School of Archaeology in Iraq in the 1953 season at Nimrud (ancient Calah/Kalḫu). The figurines were discovered in the foundations of the Burnt Palace and date approximately to the reign of Adad-nīrārī III (810–783 BCE). Their function was a part of an apotropaic ritual to protect places of residence from evil spirits and enemies. This paper aims to bring to light these figurines in the Institute’s collection by offering a descriptive catalogue and an explanation of their use in Assyrian magic for the journal’s readership.